Aurora Gutiérrez Galante Semblante de una Maestra a su paso por La Albericia (Cantabria), en el Centenario de su Nacimiento (1913-2013). // Aurora Gutiérrez Galante A teacher´s profile as she passes through the Albericia (Cantabria), in the centenary of her birth (1913-2013). - Pedro Arce Diez (Consejería de Educación, Cultura y Deporte del Gobierno de Cantabria (CRIEME), 2013)
(ES) El artículo que se presenta describe el perfil profesional y social de Aurora Pérez Galante, maestra del Plan de 1914 y también del Plan Profesional de 1931, que comenzó a ejercer la docencia en 1934 y estuvo casi cuarenta y cinco años de ejercicio profesional. Dejó una especial huella en el Barrio Santanderino de La Albericia hasta el punto de dar su nombre a una de las calles. Fue reconocida con la medalla de Alfonso X el sabio por su labor docente y humana. Se involucró en los albergues sociales y en el comedor de auxilio social. Asímismo, durante su vida profesional desarrollo las labores de instructora de la Sección Femenina y Directora de centro. //(EN) This article describes Aurora Pérez Galante´s professional and social profile. She was a teacher under the Education Act 1914 and the Professional Act 1931. She began her career in 1934 and retired nearly forty-five years later. She was a well-known person in one of Santander suburbs: 'La Albericia', and one of its streets is nowadays called after her. She was awarded the Alfonso X called The Wise medal for her teaching and human work. She was involved with different charities, such as providing social assistance for people without incomes. She also got the position of instructor and then headmasterin schools under the Women´s Section, the women´s branch of the Falange political movement in Spain.